2019
DOI: 10.1039/c8sm02423e
|View full text |Cite
|
Sign up to set email alerts
|

Identifying structural signatures of shear banding in model polymer nanopillars

Abstract: Amorphous solids are critical in the design and production of nanoscale devices, but under strong confinement these materials exhibit changes in their mechanical properties which are not well understood. Phenomenological models explain these properties by postulating an underlying defect structure in these materials but do not detail the microscopic properties of these defects. Using machine learning methods, we identify mesoscale defects that lead to shear banding in polymer nanopillars well below the glass t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…In addition, it is challenging to obtain insights into the transition from cavity expansion to crack initiation and propagation using continuum mechanics models. Recent efforts in glasses, another class of disordered solids, have shown that the response and failure of the material are heavily dictated by the local packing (91) and that certain regions in the sample are more prone to failure than others (92,93). A similar question can be posed for disordered soft materials, such as polymer networks: is the local network structure important in determining the initial formation and growth of cavity sites, and what must the size of the cavity be before continuum mechanics results can be accurately applied?…”
Section: Challenges and Unmet Needsmentioning
confidence: 99%
“…In addition, it is challenging to obtain insights into the transition from cavity expansion to crack initiation and propagation using continuum mechanics models. Recent efforts in glasses, another class of disordered solids, have shown that the response and failure of the material are heavily dictated by the local packing (91) and that certain regions in the sample are more prone to failure than others (92,93). A similar question can be posed for disordered soft materials, such as polymer networks: is the local network structure important in determining the initial formation and growth of cavity sites, and what must the size of the cavity be before continuum mechanics results can be accurately applied?…”
Section: Challenges and Unmet Needsmentioning
confidence: 99%
“…The analysis of the simulation results demonstrated the key role of surface defects in leading to pillar failure. 91 The experiments using spheres, dimers and ellipses demonstrated that a naive implementation of the ''softness'' concept worked reasonably for spheres and ellipses but quite poorly for dimers. Harrington and coworkers modified the family of structure functions in order to better match the arrangements of anisotropic particles.…”
Section: Supervised Learning Using Dynamicsmentioning
confidence: 99%
“…89 Subsequent studies have applied the learning of ''softness'' to simulations of thin polymer films and pillars and to the analysis of granular experiments using spheres, dimers and ellipsoids. [90][91][92] In the former case, Sussman and coworkers found that the enhanced dynamics close to the surface of a polymer thin film is uncorrelated with the ''softness'' parameter. The SVM approach worked as before for predicting which sites would be likely to move, it just failed to identify any changes close to the free surface (or to the substrate).…”
Section: Supervised Learning Using Dynamicsmentioning
confidence: 99%
“…48 Convolutional neural networks, which use convolutional layers in addition to the fully connected layers that characterize a basic feed forward network, have been shown to excel at computer vision tasks ranging from assessing cancer risk in radiology scans to galaxy morphology classification in telescope images. 29,49,50 As explained in §I, CNNs have also been used to classify a variety of materials, including crystal structures and Ising model configurations.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…There have also been some recent studies that have successfully used machine learning to uncover previously unknown relationships between structure and dynamics in glassy materials. [22][23][24][25][26][27][28][29][30] In these approaches, a supervised machine learning algorithm, called the support vector machine, is used to define a metric, called "softness," that identifies populations of particles that are likely to dynamically rearrange. In this context, "softness" is used to link structure and dynamics, but it is not used to directly identify local structural features or to classify different material structures.…”
Section: Introductionmentioning
confidence: 99%